100 Years of Insulin: A Historical Perspective - Pinto, Gabrielle Barbosa; Junior, Ivaldo Itabaiana; Magalhães, Jorge Lima; de Souza Antunes, Adelaide Maria (Current Topics in Medicinal Chemistry, 2025)
BackgroundDiabetes mellitus, a metabolic disease characterized by high blood glucose levels, has increased dramatically in recent years, prompting the need for more affordable diagnoses and treatments.ObjectiveThis study aimed to conduct a brief historical and theoretical review on the development of insulin.MethodsScientific and technological data have been retrieved and analyzed with a focus on the development of the active pharmaceutical ingredient insulin and insulin-based medicines. Data have been retrieved from the PubMed database available via the CAPES portal.ResultsDiabetes is one of the oldest diseases in the world. The year 2021 marked the 100th anniversary of the discovery of insulin, which transformed diabetes from a fatal disease into a chronic disease. The extraction and purification of insulin from bovine or porcine pancreases from slaughterhouses has enabled the pharmaceutical industry to produce insulin on a large scale. The introduction of insulin analogs in 1996 expanded the options. Currently, commercial insulin consists of human insulin and/or human insulin analogs.ConclusionThe state-of-the-art and technological development of insulin over the last 100 years has been presented in this work. The development of new pharmaceutical technologies has led to the obtainment of improved versions of insulin, as well as the emergence of different types of insulin. Alongside the innovations in the development of the active ingredient and related medicines, new formulations, methods, and routes of administration have emerged based on the pharmacodynamic, pharmacokinetic, and pharmacotechnical modulations of the drug.
Keywords: diabetes